Production of okra seedlings under increasing doses of vermicomposting manure (Research, Society and Development, 2020)
The production of vegetable seedlings represents one of the most important stages of the production system. However, studies on this line of research are still scarce for okra, particularly when tested organic sources, such as vermicomposting manure. Given this, the objective was to evaluate the performance of increasing doses of vermicomposting manure on the production of okra seedlings. The experiment was conducted in a completely randomized design, with six treatments, five replications and one plant per plot. The treatments consisted of increasing doses of vermicomposting slurry (0, 50, 100, 150, 200 and 250 mL L-1). After 23 days of sowing, the following variables: number of leaves; plant height; neck diameter; root length; root volume; fresh mass of the aerial part and the root system; dry mass of the aerial part and the root system; aerial part dry mass / dry mass ratio of the root system; Dickson's quality score. The application of 50 mL L-1 of vermicomposting slurry provided better development of okra seedlings.